THE EFFECTS OF PLANNING CONDITIONS ON PRIMARY SCHOOL ESL PUPILS’ NARRATIVE WRITING - Ma, Fei Fan; Zainal, Azlin Zaiti (Indonesian Journal of Applied Linguistics, 2018)
The present study investigates the writing performance in terms of language complexity, accuracy and fluency (CAF) and the pupils’ perceptions of their performance under different planning conditions and the relationship between pupils’ perceptions and their performance. There were 78 ESL pupils from a Chinese primary school in Malaysia who were grouped into three planning conditions:1) pre-task planning, 2) on-line planning and 3) no planning groups. This study employs a variety of data collection methods that include the collection of pupils’ written tasks and questionnaire surveys. The results of the study indicate that planning conditions did not have significant impacts on pupils’ writing performance except for the effect of pre-task planning on pupils’ written fluency. The results also differ greatly from numerous previous studies, which have been mainly conducted on adult writers. The present study also shows that pupils’ perceptions are partially related to their writing performance. The reasons for such contradictions are discussed. The findings have implications for the teaching of writing in the ESL context.